Pengaruh Pendidikan Pengalaman Kerja Sistem Kerja Kontrak dan Pengelolaan Sumber Daya Manusia terhadap Kualitas Tenaga Kerja pada PT Srikandi Mandiri Duta Mulia Yogyakarta - Mariani Dela Seran; Prayekti Prayekti (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The purpose of this research is to find out the influence of education, work experience, contract work system and HR management on the quality of pt. Srikandi Mandiri Duta Mulia. The research method used in this study is descriptive quantitative by using a statistical correlation of multiple regressions. Popolasi in this study is the entire workforce available at PT. Srikandi Mandiri Duta Mulia, with a sample of 53 respondents. The results stated that education, work experience, contract work systems and HR management have a positive influence both partially and simultaneously on the quality of the workforce. Keywords: education, work experience, contract work system, HR management, Quality of work.